Acupuncture for the treatment of radiation-induced xerostomia among patients with cancer: A protocol for a systematic review and meta-analysis. Issue 24 (12th June 2020) - Chen, Rumeng; Gao, Yang; Qiu, Xianliang; Hong, Peipei; Zhou, Dongqi; Chen, Qiu
Abstract: Background: With the number of cancer patients growing, radiotherapy and chemotherapy have been a necessary treatment. Unfortunately, there are many side effects after radiation and chemotherapy, one of which is xerostomia that always harasses patients. Although there are many ways of treatment of xerostomia, they have many disadvantages. With the rare side effects and the excellent effect, acupuncture has been widely applied to dry mouth after radiotherapy, but it has not been recognized as the standard treatment. Because acupuncture prescription is mostly different and the sample size of studies is small, we need more high-quality meta-analysis to provide relatively reliable evidence for the treatment of radiation-induced xerostomia. The objective of this study is to assess the curative effect of acupuncture treatment of cancer patients after radiotherapy and provide more reliable evidence for acupuncture treatment of xerostomia after radiotherapy for cancer patients. Methods: We will search the following databases: CENTRAL (The Cochrane Central Register of Controlled Trials), MEDLINE, EMBASE, PubMed, CNKI (China National Knowledge Infrastructure), VIP (China Science and Technology Journal Database), Wan Fang Data Knowledge Service Platform. At any rate, 2 review authors will assess all randomized controlled trials (RCTs), seemingly conformance to the inclusion criteria, to confirm qualification, determine the risk of bias and extract data using a running data extraction form. The revolution of disagreements is a discussion. We will use the approach recommended by Cochrane reviews to assess the bias in studies. Risk ratios (RR) and 95% confidence intervals (CIs) will be used to assess the treatment effects of an intervention for dichotomous results. We will use mean differences (MD) and standard deviation (SD) to aggregate the data of every trial for continuous results. The heterogeneity test of Cochran and quantification of the I 2 statistic will be used to assess the variation of treatment effects. Only if there are studies of semblable comparisons reporting the same results, we will conduct a meta-analysis. Results: From the study, we will evaluate the efficacy of acupuncture for xerostomia patients who has cancer and been treated by radiation. Conclusion: The conclusion of this study will be the evidence, which can ensure the efficacy of acupuncture for cancer patients with radiation-evoked xerostomia among and provide guidance for the treatment of xerostomia. INPLASY registration number: INPLASY202040211.